Respuesta :

Answer:

The following two equations model this relationship.

  • [tex]\:\sqrt[3]{r}=\:\frac{k}{s^2}[/tex]
  • [tex]\:\:s^2\:r^{\frac{1}{3}}=\:\frac{k}{s^2}[/tex]  

Step-by-step explanation:

We know that when 'y' varies inversely with 'x', we get the equation

y ∝ 1/x

y = k / x

k = yx

where 'k' is called the 'constant of proportionality'.

In our case, it is given that the cube root of 'r' varies inversely with the square of 's', then

[tex]\sqrt[3]{r}[/tex] ∝ [tex]\frac{1}{s^2}[/tex]

[tex]\:\sqrt[3]{r}=\:\frac{k}{s^2}[/tex]

or

[tex]\:\:s^2\:r^{\frac{1}{3}}=\:\frac{k}{s^2}[/tex]          ∵ [tex]\sqrt[3]{r}=r^{\frac{1}{3}}[/tex]

Therefore, the following two equations model this relationship.

  • [tex]\:\sqrt[3]{r}=\:\frac{k}{s^2}[/tex]
  • [tex]\:\:s^2\:r^{\frac{1}{3}}=\:\frac{k}{s^2}[/tex]  

Answer:

a and b it was right on the test

Step-by-step explanation: